Race and ethnicity in educational intervention research: A systematic review and recommendations for sampling, reporting, and analysis. (November 2020) - Gaias, Larissa M.; Duong, Mylien T.; Pullmann, Michael D.; Brewer, Stephanie K.; Smilansky, Michelle; Halbert, Mallory; Carey, Cathea M.; Jones, Janine
Abstract: Racial/ethnic educational disparities remain a pervasive and intractable issue facing the US education system. To eliminate these disparities, educational research must consistently attend to race/ethnicity, particularly when examining the effects of educational practices, programs, and policies. The goal of the current review was to examine the prevalence with which educational intervention research 1) reports on race/ethnicity, 2) includes samples representative of the racial/ethnic composition of US public schools, and 3) examines the potential for reducing racial/ethnic disparities. We coded a randomly selected 96 (13%) of all educational intervention studies that met What Works Clearinghouse (WWC) standards for rigorous research in the areas of students with disabilities, literacy, early childhood education, English Language Learners, mathematics, character education, and dropout prevention. We also identified and coded 210 meta-analyses in these topic areas. Because our aim was to describe the extent to which current educational intervention research, as a whole, focuses on race/ethnicity in reporting, sampling, and analysis, we included studies even when reducing disparities was not an explicit focus. Results indicated that 27% of empirical studies and 94% of meta-analyses did not report race/ethnicity. Hispanic/Latinx, Asian/Pacific Islander, and Native American youth were underrepresented in research samples. Only 19% of empirical studies and 6% of meta-analyses conducted analyses to examine the potential impact for reducing racial/ethnic disparities. This review demonstrates a clear need for researchers to be more intentional when designing and evaluating educational interventions to reduce pervasive racial/ethnic inequities in educational outcomes. Highlights: Most empirical studies of education interventions report racial/ethnic composition. Few meta-analyses of education interventions report racial/ethnic composition. Black and White participants are included in most education intervention studies. Asian, Native American, and Latinx populations are underrepresented. Few education intervention studies examine effectiveness for reducing disparities.